1992
DOI: 10.2307/3578489
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Nature of DNA Damage and Cell Death Induced by 125 I Decay

Abstract: Chinese hamster ovary cells were synchronized at the G1/S-phase boundary of the cell cycle and pulse-labeled for 10 min with 125I-iododeoxyuridine 30 min after entering the S phase. Cell samples were harvested for freezing and 125I-decay accumulation at intervals ranging from 15 to 480 min after termination of labeling. The survival data showed a marked shift from cell killing characteristic of low-LET radiation to that more characteristic of killing by high-LET radiation with increasing intervals between DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…For the 125 I, Geselowits et al (50) quantified the toxicity of radiation of the [ 125 I]IUdR incorporated in the nucleus of CHO cells in the early S phase. The result was a D 37 between 40 and 165 decays/cell of 125 I, which is consistent with the work of Hofer et al (52) who reported a mean value of ~100 decays/ cell. On the other hand, Humm and Charlton (29) derived the following relationship between the total number of DSB (N DSB ) and the initial number of radioactive atoms (N 0 ) attached to DNA base pairs (and hence the activity) which are needed to produce such DSB, as follows:…”
Section: Initial Activity Of 64 Cu To Cause Lethal Damagesupporting
confidence: 92%
“…For the 125 I, Geselowits et al (50) quantified the toxicity of radiation of the [ 125 I]IUdR incorporated in the nucleus of CHO cells in the early S phase. The result was a D 37 between 40 and 165 decays/cell of 125 I, which is consistent with the work of Hofer et al (52) who reported a mean value of ~100 decays/ cell. On the other hand, Humm and Charlton (29) derived the following relationship between the total number of DSB (N DSB ) and the initial number of radioactive atoms (N 0 ) attached to DNA base pairs (and hence the activity) which are needed to produce such DSB, as follows:…”
Section: Initial Activity Of 64 Cu To Cause Lethal Damagesupporting
confidence: 92%
“…Examples of track structure analysis and applications have been proposed by Nikjoo [198]. In this context, the extension of microdosimetry to energy deposition in small volumes of some tens of nm may be relevant since damage to higher order structures than molecular DNA could contribute to and perhaps be required for cell killing [192]. Finally, a phenomenological approach combining microdosimetric distributions with biological response functions (see 2.2) is not restricted to µm simulated biological targets.…”
Section: Energy Deposition In Cells By Short-range Electronsmentioning
confidence: 99%
“…One reason for considering a mechanistic approach, i.e. one involving elementary physical and if possible molecular processes, is the observation of an unexpected type of DNA damage, which cannot be classically interpreted as high-or low-LET damage even when Auger-emitters are incorporated into DNA [192].…”
Section: Energy Deposition In Cells By Short-range Electronsmentioning
confidence: 99%
“…There are strong grounds for critical evaluation of both the track physics model and conventional risk models. A recent paper by Hofer et al [17] suggests that cell death is associated with higher order structures in the cell nucleus than DNA segments. This may alter perspectives in some conventional risk models.…”
mentioning
confidence: 99%